Programs of Active Aging – A Relation between BMI and Triglycerides - Honório, Samuel (2013)
Objective: To enhance the importance of physical activity programs for elderly and their influence on BMI and triglycerides. Methods: The sample consisted of 91 elderly individuals, 63 females and 28 males aged between 65 and 78 years of age. All seniors practice water activities, including swimming and gymnastics. Were analyzed with respect to two aspects: BMI, Triglycerides and practice time, seniors who were physically active at least 2 months, and seniors who maintained habits of physical activity between 2 and 6 months and still accumulated 30 or more minutes of other activities. We have established contingency tables were confronted where the variables described in the analysis. Results: It was found that elderly who maintained physical activity programs were broader outnumbered those who were overweight and obesity rates in Table I of BMI, and lower triglycerides values. Conclusions: We concluded therefore that physical activity programs that contemplate 2 or more hours per week, duly organized and systematized constitute a positive factor in combating inactivity and turn into a more active and cheerful elderly.